2022
DOI: 10.1186/s40164-022-00267-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased TOX expression associates with exhausted T cells in patients with multiple myeloma

Abstract: Previous studies have shown increased aberrant expression of immune checkpoint (IC) proteins, such as programmed cell death receptor-1 (PD-1) and T cell immunoglobulin mucin-domain-containing-3 (Tim-3) on T cells from patients with multiple myeloma (MM), which result in T cell exhaustion and dysfunction. However, little is known about the mechanism regulating aberrant IC protein expression. In this study, we analyzed the expression of TOX (thymocyte selection-associated HMG BOX), a crucial transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…It is known that T cell dysfunction is related to the cancer immune microenvironment ( 19 ). In previous studies, researchers have observed a greater impact on T cell suppression in BM compared with that in PB in leukemia and MM patients, which was evident from the higher percentage of PD-1+/Tim-3+ T cells in the BM ( 4 , 42 , 43 ). Interestingly, these results unlike the findings of higher PD-1+/Tim-3+ T cells and TOX+ T cells in BM compared with that in PB in MM patients ( 10 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is known that T cell dysfunction is related to the cancer immune microenvironment ( 19 ). In previous studies, researchers have observed a greater impact on T cell suppression in BM compared with that in PB in leukemia and MM patients, which was evident from the higher percentage of PD-1+/Tim-3+ T cells in the BM ( 4 , 42 , 43 ). Interestingly, these results unlike the findings of higher PD-1+/Tim-3+ T cells and TOX+ T cells in BM compared with that in PB in MM patients ( 10 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that Tregs accumulate in MM, and this is closely related to high mortality and reduced survival time, which is consistent with our findings (45, 47, 48). In addition, we previously reported higher expression of immune inhibitory proteins including PD-1, Tim-3, and TOX in Tregs in hematologic malignancies that negatively impact T cell immunosuppressive functions (4,36,42). Anna et al found that patients with MM with higher frequencies of Tregs had inferior survival and a distinct Treg immune checkpoint profile (i.e., increased PD-1, LAG-3) (49).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…TOX exhausts CD8 + T lymphocytes in mouse models (infection ( 13 15 ) or tumor models) or human cancers, including melanoma, non-small cell lung carcinoma ( 16 ), colorectal cancer ( 17 ), liver cancer ( 18 ), bladder cancer, oral squamous cell carcinoma ( 19 ), acute myeloid leukemia ( 18 , 20 ), multiple myeloma ( 21 ), and non-Hodgkin’s lymphoma ( 22 ) ( Figure 1 ) ( Table 1 ).…”
Section: Tox Expression During Thymocyte Developmentmentioning
confidence: 99%
“…Higher counts of TOX + Treg subsets in the bone marrow may be helpful in mediating immunosuppressive microenvironment in the bone marrow ( 7 ). The proportion of the TOX + Treg subgroup is increased in patients with non-Hodgkin’s lymphoma ( 22 ), multiple myeloma (MM) ( 21 ), or de novo AML ( 18 ), and this phenomenon results in Treg activation instead of Treg exaustion. Fusobacterium nucleatum may aggravate rectal cancer by inhibiting antitumor T cell-mediated adaptive immunity.…”
Section: Tox Is Intrinsically and Extrinsically Involved In The Devel...mentioning
confidence: 99%